Smart Biomedical and Physiological Sensor Technology X 2013
DOI: 10.1117/12.2016020
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible hydrogel membranes for the protection of RNA aptamer-based electrochemical sensors

Abstract: Electrochemical-aptamer based (E-AB) sensors represent a universal specific, selective, and sensitive sensing platform for the detection of small molecule targets. Their specific detection abilities are afforded by oligonucleotide (RNA or DNA) aptamers employed as electrode-bound biorecognition elements. Sensor signaling is predicated on bindinginduced changes in conformation and/or flexibility of the aptamer that is readily measurable electrochemically. While sensors fabricated using DNA aptamers can achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 22 publications
4
11
0
1
Order By: Relevance
“…RIs are ~50 kDa proteins that stoichiometrically bind (1:1) to RNases inhibiting nucleolytic activity. 10,24 The observation of protected sensor elements in RI treated serum is consistent with previously published reports 3,12,13,15,25 and is a clear indication that nuclease activity is the dominant cause of sensor failure.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…RIs are ~50 kDa proteins that stoichiometrically bind (1:1) to RNases inhibiting nucleolytic activity. 10,24 The observation of protected sensor elements in RI treated serum is consistent with previously published reports 3,12,13,15,25 and is a clear indication that nuclease activity is the dominant cause of sensor failure.…”
Section: Resultssupporting
confidence: 92%
“…We previously reported the protection of RNA aptamer sensor surfaces with a polyacrylamide film, however, even with these films, we observed a reduction of ~30% current before stabilization. 15 Here we find that the collagen-based membrane provides superior protection compared to polyacrylamide. However, if we employ the collagen I coated sensors incubated with serum at a pH ~ 10, a pH at which the RI should be inactivate, we observed a significant signal decrease (~30 %) over the time course of 6 hours, similar to the report by Schoukroun-Barnes et al using a polyacrylamide membrane 15 (Figure 6).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, it was demonstrated that the direct contact of aptamer-based electrochemical biosensors with biological complex culture media may affect sensors performance and stability due to the serum protein-dependent degradation of the sensing oligonucleotides; this, in turn, leads to the need for sample pretreatments or more complex chemical modification of the aptamers [239,[266][267][268][269].…”
Section: Aptamer-based Biosensorsmentioning
confidence: 99%
“…Para o estudo mostrado em [39] houve um processo de otimização onde foram testadas diferentes configurações para uma amostra de RNA de 26 bases nitrogenadas, imobilizadas na superfície de um eletrodo de ouro com a finalidade de detectar a ligação de tobramicina, incluindo a variação das frequências de aquisição testadas, e a variação das diferentes formas conformacionais da molécula utilizada como alvo. Para o biossensor otimizado foi encontrada uma faixa dinâmica de 220 nM ~ 42 μM e um limite de detecção de 220nM.…”
Section: Entendendo a Variação Vista Nos Diagramas De Nyquistunclassified